Systematic Journal Review: Mechanical Durability Of L-PRF Organic Material At Body Temperature During The Wound Healing Phase (14 Days) Of Tympanic Membrane Perforation And Myringoplasty Surgery - Antonius Christanto; Risya Cilmiaty; Made Setiamika; Ratih Dewi Yudhani; Paramasari Dirgahayu; Eti Poncorini Pamungkasari; Ida Nurwati (Universitas Ibn Khaldun Bogor, 2026)
The purpose of this study is to evaluate the viability and structural stability of L-PRF at 37°C over 14 days. It aims to determine its sustained growth factor release and potential effectiveness in regenerative clinical applications. This research employed a Systematic Journal Review (SJR) approach, surveying articles from databases such as PubMed, Scopus, and Google Scholar using specific keywords related to L-PRF. A total of 25 articles meeting the inclusion criteria were filtered for analysis. Furthermore, common experimental methods described in the literature include the preparation of L-PRF via blood centrifugation and viability testing over 14 days at 37°C, encompassing analysis of microscopic structure, mechanical properties, and biochemical and biological activities. Literature analysis indicates that L-PRF is an effective autologous biomaterial for regenerative applications, capable of continuously releasing growth factors such as PDGF, TGF-β, VEGF, and IGF for up to 14 days at body temperature. Cell viability within the fibrin matrix is maintained, positioning L-PRF as a promising active biological scaffold for accelerating tissue healing. Although challenges such as matrix degradation persist, modification strategies and optimized centrifugation protocols can enhance the effectiveness and durability of L-PRF in clinical applications.